Regenerative Engineering-The Convergence Quest. (14th January 2018) - Laurencin, Cato; Nagiah, Naveen
ABSTRACT: We define Regenerative Engineering as a Convergence of Advanced Materials Science, Stem Cell Science, Physics, Developmental Biology, and Clinical Translation. We believe that an "un-siloed' technology approach will be important in the future to realize grand challenges such as limb and organ regeneration. We also believe that biomaterials will play a key role in achieving overall translational goals. Through convergence of a number of technologies, with advanced materials science playing an important role, we believe the prospect of engaging future grand challenges is possible. Regenerative Engineering as a field is particularly suited for solving clinical problems that are relevant today. The paradigms utilized can be applied to the regeneration of tissue in the shoulder where tendon and muscle currently have low levels of regenerative capability, and the consequences, especially in alternative surgical solutions for massive tendon and muscle loss at the shoulder have demonstrated significant morbidity. Polymer, polymer-cell, and polymer biological factor, and polymer-physical systems can be utilized to propose a range of solutions to shoulder tissue regeneration. The approaches, possibilities, limitations and future strategies, allow for a variety of clinical solutions in musculoskeletal disease treatment.